The p-Anisaldehyde/β-cyclodextrin inclusion complexes as a sustained release agent: Characterization, storage stability, antibacterial and antioxidant activity. (February 2022) - Lin, Ying; Huang, Ran; Sun, Xiuxiu; Yu, Xi; Xiao, Ying; Wang, Ling; Hu, Wenzhong; Zhong, Tian
Abstract: In order to develop a biodegradable agent for food preservation, β-cyclodextrin (β-CD) inclusion complexes containing p -Anisaldehyde (PAA) were prepared using co-precipitation method. Physical properties including moisture content, bulk density, hygroscopicity, entrapment efficiency and loading capacity of the inclusion complexes showed considerable results for food applications. SEM and particle size test showed notably difference between the prepared inclusion complexes and the other formulations including the raw β-CD, physical mixture, and the recrystallized β-CD in both shape and size distribution. FTIR, XRD, TGA and DTA were also carried out and confirmed the formation of inclusion complexes and inhibition of the volatility of encapsulated PAA. As a potential preservation agent, inclusion complexes demonstrated a sustained released behavior in phosphate buffer saline (PBS). Comparing with pure PAA, the inclusion complexes presented a better storage stability in low humidity environment, a higher antioxidant activity, and equal MICs against Escherichia coli and Staphylococcus aureus . Highlights: The p -Anisaldehyde was encapsulated into β-CD by co-precipitation method. Various characterization techniques confirmed the formation of inclusion complex. Encapsulation ensured the slow release of p -Anisaldehyde from inclusion complexes. The inclusion complex has better storage stability than pure p -Anisaldehyde. The inclusion complex showed considerable antibacterial and antioxidant activity.